Exploration of Local Wisdom as a Disaster Communication Strategy: Building Resilience of the People - Muh. Resa Yudianto Suldani; Gilang Bintang; Dyandra Erlangga D (Borong Newinera Publisher, 2026)
This study aims to identify forms of local wisdom related to disasters and the challenges to their preservation in Morowali Regency. Data were obtained through in-depth interviews with informants from various indigenous communities, community leaders, and traditional practitioners, then analyzed using a qualitative approach using NVivo software. The results indicate that the Morowali local community maintains a number of traditional practices that serve as disaster mitigation and understanding tools, including agricultural rituals to ensure soil fertility, traditional ndengu-ndengu chant used during extra ordinary accident or disasters, and legends and stories that mark extreme natural events. However, the preservation of local wisdom faces various challenges, such as lack of interest among the young generation, limited documentation, the influence of modernization, and a lack of support from government institutions. This study emphasizes the importance of integrating local wisdom with modern disaster mitigation programs and cultural preservation efforts to ensure that traditional knowledge remains relevant and beneficial to the community in facing disaster risks.